Adaptive in vivo device for theranostics of inflammation: Real-time monitoring of interferon-γ and aspirin. (1st January 2020) - Cao, Chaomin; Jin, Ronghua; Wei, Hui; Liu, Zhongning; Ni, Shengnan; Liu, Guo-Jun; Young, Howard A.; Chen, Xin; Liu, Guozhen
Abstract: Cytokines mediate and control immune and inflammatory responses. Complex interactions exist among cytokines, inflammation, and the innate and adaptive immune responses in maintaining homeostasis, health, and well-being. On-demand, local delivery of anti-inflammatory drugs to target tissues provides an approach for more effective drug dosing while reducing the adverse effects of systemic drug delivery. This work demonstrates a proof-of-concept theranostic approach for inflammation based on analyte-kissing induced signaling, whereby a drug (in this report, aspirin) can be released upon the detection of a target level of a proinflammatory cytokine ( i.e., interferon-γ (IFN-γ)) in real time. The structure-switching aptamer-based biosensor described here is capable of quantitatively and dynamically detecting IFN-γ both in vitro and in vivo with a sensitivity of 10 pg mL −1 . Moreover, the released aspirin triggered by the immunoregulatory cytokine IFN-γ is able to inhibit inflammation in a rat model, and the release of aspirin can be quantitatively controlled. The data reported here provide a new and promising strategy for the in vivo detection of proinflammatory cytokines and the subsequent therapeutic delivery of anti-inflammatory molecules. This universal theranostic platform is expected to have great potential for patient-specific personalized medicine. Statement of Significance: We developed an adaptive in vivo sensing device whereby a drug, aspirin, can be released upon the detection of a proinflammatory cytokine, interferon-γ (IFN-γ), in real time with a sensitivity of 10 pg mL −1 . Moreover, the aspirin triggered by IFN-γ depressed inflammation in the rat model and was delivered indirectly through blood and cerebrospinal fluid or directly to the inflammation tissue or organ without adverse gastrointestinal effects observed in the liver and kidney. We envision that, for the first time, patients with chronic inflammatory disease can receive the right intervention and treatment at the right time. Additionally, this technology may empower patients to monitor their personalized health and disease management program, allowing real-time diagnostics, disease monitoring, and precise and effective treatments. Graphical abstract: Image, graphical abstract